Ofícios e pequena indústria em Penafiel: caldeireiros - Soeiro, Teresa (2022)
Following the overview of the coppersmith craft in the country we now focus on Penafiel where, since the 1840s, it gained unprecedented visibility due to the setting up of a professional coppersmith, Manuel Cunha, in the city. We trace the "Coppersmiths Cunha" family path investigating how they settled in, the strategies adopted to ensure economic viability, and the transmission of know-how from generation to generation. Later, with the Penafiel region needs met, the newer generations set out to conquer new markets. In this expansion process they established coppersmith shops all over Entre-Douro-e-Minho. These were in great demand when the family, at the turn of the 20th century, added to their traditional activity the preparing and installation of complex alembics, and the making and repairing of sprayers for agricultural use that became indispensable since the blight emergence.